SPACE-ANALYSIS AS THE BASIS FOR CHOOSING AN ENTERPRISE DEVELOPMENT STRATEGY IN THE MINERAL WATER MARKET - Bochko , O.Yu.; Kuziak , V.V.; Hryniv , N.T. (The actual problems of regional economy development, 2022)
The article reveals the current state of the mineral water market. Research relevance of the mineral water market is due to the fact that the market is featured with cheapness, affordability, and doesn't require high consumer profitability, which arouses the interest of state authorities, strata of the population, and organizations to study this issue. The purpose of writing this article is to conduct a SPACE-analysis, which is the basis for choosing a strategy for enterprise development in the mineral water market. Various general and special research methods were used during the writing of this scientific article. The inductive and deductive methods were used to conduct the SPACE analysis of the MMWF (Myrhorod Mineral Water Factory) “Oscar”. The analysis of the mineral water market of Lviv region was carried out with the help of economic analysis and comparison. The graphical method was used to visualize the petal diagram of the SPACE analysis MMWF “Oscar”.An abstract-logical method was used for theoretical generalizations and drawing conclusions. It is substantiated in the article the place of PJSC “MMWF Oscar” in the mineral water market and proposed a strategy for its development. SPACE analysis has been performed, which allows to classify and analyze the internal and external environment of the enterprise. The petal diagram of SPACE-analysis for PJSC “MMWF Oscar” was built. The competitive position of the studied enterprise characterized by the use of offensive strategy (which is applied if the available production advantages and the overall development of the enterprise are provided and it is an unstable situation within the industry) was substantiated. It is proved that the main actions of the company in such conditions are aimed at finding financial resources and expanding the sales system. The scientific novelty of the publication lies in the implementation of SPACE-analysis as the basis for choosing the strategy of enterprise development in the mineral water market and building a petal diagram of the SPACE-analysis of PJSC 'MMWF OSCAR'. Environmental stability (ES), industry strength (IS), competitive advantage (CA), and financial strength (FS) factors were investigated. The obtained information will contribute to a more deep understanding of the company's position in the mineral water market in modern conditions.